Discontinuities concentrate mobile predators: quantifying organism–environment interactions at a seascape scale. Issue 2 (26th February 2016) - Kennedy, Cristina G.; Mather, Martha E.; Smith, Joseph M.; Finn, John T.; Deegan, Linda A.
Abstract: Understanding environmental drivers of spatial patterns is an enduring ecological problem that is critical for effective biological conservation. Discontinuities (ecologically meaningful habitat breaks), both naturally occurring (e.g., river confluence, forest edge, drop‐off) and anthropogenic (e.g., dams, roads), can influence the distribution of highly mobile organisms that have land‐ or seascape scale ranges. A geomorphic discontinuity framework, expanded to include ecological patterns, provides a way to incorporate important but irregularly distributed physical features into organism–environment relationships. Here, we test if migratory striped bass ( Morone saxatilis ) are consistently concentrated by spatial discontinuities and why. We quantified the distribution of 50 acoustically tagged striped bass at 40 sites within Plum Island Estuary, Massachusetts during four‐monthly surveys relative to four physical discontinuities (sandbar, confluence, channel network, drop‐off), one continuous physical feature (depth variation), and a geographic location variable (region). Despite moving throughout the estuary, striped bass were consistently clustered in the middle geographic region at sites with high sandbar area, close to channel networks, adjacent to complex confluences, with intermediate levels of bottom unevenness, and medium sized drop‐offs. In addition, the highest striped bass concentrations occurred at sites with the greatest additive physical heterogeneity (i.e., where multiple discontinuities co‐occurred). The need to incorporate irregularly distributed features in organism–environment relationships will increase as high‐quality telemetry and GIS data accumulate for mobile organisms. The spatially explicit approach we used to address this challenge can aid both researchers who seek to understand the impact of predators on ecosystems and resource managers who require new approaches for biological conservation.